Analisis Penilaian Harga Saham Menggunakan Metode Dividend Discount Model (DDM) Pada Perusahaan Asuransi Yang Terdaftar Di Bursa Efek Indonesia Periode 2019 – 2021 - Manda, Gusganda Suria; Sari, Chairunisa Arunilam; Syarafi, Dwi Tio (Peneliti.net, 2024)
This research aims to analyze the intrinsic value of insurance sector companies listed on the Indonesia Stock Exchange for the period 2019 to 2021 using the Dividend Discount Model (DDM). Obtained as many as 5 companies that became the research sample with the criteria of companies that distribute dividends in the period. The method used is descriptive quantitative, using secondary data, namely annual financial reports obtained through the Indonesian Stock Exchange website. The purpose of this research is to understand and analyze the results of stock valuation calculations using the Dividend Discount Model (DDM) with a constant growth model. The research results show that all shares of insurance sector companies, including LPGI, TUGU, ASDM, ASRM, and ABDA in 2019 – 2021 were undervalued because the intrinsic value was higher than the market price. In 2021, only one company, LPGI, was considered overvalued because its intrinsic value was lower than the market price. From the comparison of intrinsic value with the market price of the undervalued category, prospective investors are advised to buy a stock as an investment decision.